Holy Time and Popular Invented Rituals in Islam: Structures and Symbolism - Mansouri, Mabrouk Chibani (Al-Jamiah Research Centre, 2018)
This paper tackles three popular invented rituals in the early centuries of Islam performed in the seventh and eighth months of the Islamic calendar; Rajab and ShacbÄn, namely the sacrifices of faraca and catÄ«ra, fasting and prayers. In the light of sociocultural and psycho-cultural perspectives, the paper discusses the cultural and spiritual perceptions of time and space in Islam, and the reasons that make specific settings fertile soils suitable for inventing new rituals. Then, it analyses the structures and symbolism of these rituals as a means of dialogical relationship with the self, the other, and the group. The paper also sheds light on the piety folk developed by Sufism as a response to spiritual void and psychological needs that lead Muslims to invent new forms of worship. The paper will, then, analyze the scholarly debate over the legitimacy of these invented rituals and the festivities associated with them, and tackle the interpretative strategies to approve them in a long dialectical process with âpuritanâ Muslims. In the end, it discusses the relationship of invented rituals to the embedded structure of power and it sheds light on the reasons behind the escalation of practicing these invented rituals in recent decades in the Arab Islamic world.[Tulisan ini mengkaji tiga ritus ibadah di awal abad perkembangan Islam yaitu perayaan bulan Rajab dan Shaâban, puasa dan shalat. Dengan pendekatan sosial budaya dan psikologi budaya, tulisan ini membahas persepsi budaya dan spiritual mengenai waktu dan ruang dalam Islam, serta menjelaskan setting khusus yang membuat reka cipta ritual baru. Disamping itu tulisan ini juga membahas struktur dan simbol ritual teresebut sebagaiÂ perangkat dialog dengan diri sendiri, pihak lain dan kelompok. Tulisan ini juga membahas pengembangan bentuk kesalehan kaum sufi sebagai respon kebutuhan psikologis dan pemenuhan spiritual yang menuntun umat muslimÂ mereka cipta bentuk persembahan baru. Termasuk perdebatan para ulamaÂ mengenai legitimasi perayaan tersebut dan proses dialog dengan kelompok puritan. Di bagian akhir akan dijelaskan hubungan ritual tersebut dengan struktur kekuasaan yang melekat dan menguatnya praktik tersebut beberapa dekade terakhir terutama di dunia muslim Arab.]Â